MENIMBANG REGULASI SKB 2 MENTERI DALAM TERANG SEJARAH GEREJA - Deky Nofa Aliyanto (Sekolah Tinggi Teologi Aletheia, 2021)
SKB 2 Menteri concerning the Establishment of House of Worship is stipulated on March 21, 2006, by the Minister of Religion and Minister of Home Affairs. Since its establishment, there are some churches affected by the regulations. This study attempts to construct the church's current attitude towards this reality based on church history in 30-500 AD. This study uses a qualitative approach with interactive analysis, namely data collection, data presentation, and data reduction, to draw a conclusion. The results of the study include: based on history, the church today must view the Joint Ministerial Decree on the Establishment of Houses of Worship as regulations aimed at maintaining tolerance among religious communities in Indonesia. However, it was found that this regulation was used by people or persons who were not responsible for suppressing the existence of some churches in Indonesia. Reflecting on history, today's church should make the challenge a stepping stone to experience the quality of faith growth in the congregation. The church also has the right to struggle through legal channels as stipulated in the law. Whatever the outcome, the church must guard against being involved in anarchic actions. SKB 2 Menteri Tentang Pendirian Rumah Ibadah ditetapkan pada tanggal 21 Maret 2006 oleh Menteri Agama dan Menteri Dalam Negeri. Sejak ditetapkan, terdapat sebagian gereja yang terdampak regulasi peraturan itu. Penelitian ini berupaya membangun sikap gereja masa kini terhadap realitas ini berdasarkan sejarah gereja tahun 30-500 M. Penelitian ini menggunakan pendekatan kualitatif dengan analisa interaktif yaitu penggumpulan data, penyajian data, reduksi data dan penarikan kesimpulan. Hasil penelitian mencakup: berdasarkan sejarah, gereja masa kini harus memandang SKB 2 Menteri Tentang Pendirian Rumah Ibadah sebagai peraturan yang bertujuan menjaga toleransi antar umat beragama di Indonesia. Kendatipun demikian, ditemukan bahwa peraturan ini dimanfaatkan oleh orang-orang atau oknum yang tidak bertanggung jawab untuk menekan eksistensi sebagian gereja di Indonesia. Berkaca dari sejarah, hendaknya gereja masa kini menjadikan tantangan tersebut sebagai batu loncatan untuk mengalami kualitas pertumbuhan iman jemaat. Meskipun demikian, gereja juga memiliki hak untuk berjuang melalui jalur hukum sebagaimana telah diatur dalam undang-undang. Apapun hasilnya gereja harus menjaga diri supaya tidak terlibat aksi anarkis.